Effects of combined attacks on the technical-tactical and psychophysiological performance of mixed martial arts fighters - Davidenko, I.; Kazymov, M.; Akmatova, A.; Bolotin, A.; Pronin, E.; Anisimov, M.; Ibragimov, I.; Vorozheikin, A.; Konovalov, A.; Purtova, G.; Redi, E.; Tyrina, M.; et al. (Journal of Physical Education and Sport, 2025)
Different types of martial arts (hand-to-hand combat, combat sambo, mixed martial arts (MMA), and pankration) require athletes to undergo versatile training that combines striking and wrestling techniques with sequential transitions between the combat phases: stance, grip, and ground. The key strategy in these disciplines is to use combination attacks, which allow a fighter to maintain dominance during the fight. However, the influence of combination attacks on fighters' overall effectiveness, as well as their connection to psychophysiological factors such as simple and complex visual-motor reactions (CVMRs), remains inadequately studied.